Photosynthetic electron transport and superoxide dismutase activity during natural senescence of maple leaves - Lepeduš, Hrvoje (Array, 2008)
Summary: Natural senescence of maple (Acer pseudoplatanus L.) leaves was investigated. Three types of senescing leaves were used: green (G), yellow-green (YG) and yellow (Y) ones. Down regulation of photosynthetic performance was achieved due to significant degradation of total chlorophylls, decrease in maximum quantum yield of PSII (Fv/Fm) and relative electron transport rate (rel. ETR). Also, decrease in Rubisco LSU abundance as well as degradation of rbcL gene was shown in YG and Y leaves. Senescent leaves revealed significant increase in the capacity of PSII for oxygen evolution when expressed per chlorophyll unit. This was the most probable source of reactive oxygen species (ROS) excess. The level of SOD (superoxide dismutase) activity increased 3.5-fold in Y leaves in respect to G and YG leaves. The increase in ROS level as well as in SOD activity during natural senescence of maple leaves was associated with increased level of lipid peroxidation and protein carbonyl content